Introduction: classroom discourse at the intersection of language education and materiality. Issue 1 (3rd April 2021) - Mathieu, Corinne S.; Marcos Miguel, Nausica; Jakonen, Teppo
ABSTRACT: This special issue provides a collection of research that examines the relationships between classroom materials and discourse in various second language education contexts. Together, these studies add to the field of language teaching and learning materials use research by offering new understandings of how materials – and how they are used in the classroom – can shape discourse. By utilising a wide range of theoretical and methodological approaches to explore materials use research, the contributors of the special issue demonstrate the importance of considering the material aspect of the language teaching/learning environment when studying classroom discourse. This introduction will situate the articles in the special issue in relationship to previous discourse and materials use research.